Variation at the LRRK2 locus determines the rate of disease progression in pro- gressive supranuclear palsy. Issue 6 (27th May 2022) - Jabbari, Edwin; Tan, Manuela; Jaunmuktane, Zane; Holton, Janice; Revesz, Tamas; Warner, Thomas; Lees, Andrew; Ryten, Mina; Hardy, John; Morris, Huw; ,
Abstract : Background: The genetic basis of variation in the rate of disease progression in primary tauopathies is poorly understood. Here, we have conducted a genome-wide association study (GWAS) of Progressive Supranuclear Palsy cases using survival as a marker of disease progression. Methods: Two independent, deeply-phenotyped, PSP cohorts of European ancestry underwent genotyp- ing and SNP imputation. Standard data quality control steps were used, including a MAF threshold of 1%. We used a cox-proportional hazards survival model GWAS that adjusted for sex, age at motor symptom onset, PSP phenotype and ethnicity (first three principal components). Results: 1, 001 PSP cases (2011 case-control GWAS, n=424; UCL PSP cohort, n=577) and 4, 817, 946 SNPs passed quality control steps and were available for analysis. We found a genome-wide significant signal on chromosome 12 with the lead SNP identified as rs2242367 (hazard ratio = 2.24, p-value = 7.5x10 -10 ). This signal replicated when each independent cohort was analysed separately. The risk allele at this SNP was associated with a 1 year reduction in survival. eQTL analyses revealed that rs2242367 and its tagging SNPs are eQTLs for LRRK2 expression in whole blood and brain. Conclusions: We hypothesise that the whole blood eQTL signal may impact on monocyte-derived micro- glia-like cells and that increased LRRK2 expression may result in a reactive microglia-induced pro-inflam- matory state which drives ongoing accumulation of misfolded tau protein and clinical disease progression. e.jabbari@ucl.ac.uk